(3ebOeI aj CSGSjGJ eMGSHI GdJcGdja (B/s - (3YHO GdMj, eQYjs; (3gdGd, YHO Gddg YHO GdYXje s ((3GdEScfOQjI(B: s (3GdecJH GdLGeYj GdMOjK(B, s, 2006)
(3JLO aj gPG GdcJGH (B: (3CgOGa eMGSHI GdJcGdja aj GdeGVj hGdMGVQ hGdeSJbHd , eaGgje GdJcdaI hYfGUQgG , fXe bjGS JcdaI GdEfJGL ,eONd bjGS GdJcdaI , JSLjd YfGUQ GdJcGdja , GdeMGSHI Yf GdJcdaI GdUfGYjI ZjQ GdeHGTQI hGdQbGHI YdjgG GdQbGHI Ydi GdehGQO hGdNGeGJs
Keywords: (3eMGSHI GdJcGdjas